On digitalization methods in the conservation of architectural heritage in Russian cities - Sadykova Leysan I.; Kholodova Lyudmila P. (Архитектон)
Whereas previously the basic element of architectural and historical heritage conservation was material value, the modern concept of heritage conservation is enhanced by mental value, social value, and identity. The paper reviews Russian and international legislative acts, regulations and guidelines on the identification and preservation of architectural heritage and demonstrates the use of novel digitalization methods in the conservation of surviving or physically lost architectural heritage.